2015
DOI: 10.1155/2015/195972
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pathogenic Escherichia coli and Staphylococcus aureus from Cattle and Pigs Slaughtered in Abattoirs in Vhembe District, South Africa

Abstract: Pathogenic food-borne bacteria have been associated with severe morbidity and mortality in humans and animals. This study was aimed at determining the prevalence of Staphylococcus aureus, Salmonella spp., and Escherichia coli present in cattle and pigs slaughtered in selected abattoirs in Vhembe District and at determining the susceptibility of the isolates to antibiotics. A total of 176 swab samples (28 cattle and 16 pigs) of the rump, flank, brisket, and neck of the animals were analyzed using standard micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
33
4
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 36 publications
(58 reference statements)
8
33
4
3
Order By: Relevance
“…The results were in line with those of Enumeration on total aerobic bacteria on meat; Chicken Carcasses on the number of bacteria found on chicken meat; and on micro bacteria on beef in Kigali city, Rwanda [33,17,12]. [29,30,27].…”
Section: Enumeration Of Total Aerobic Bacteriasupporting
confidence: 81%
“…The results were in line with those of Enumeration on total aerobic bacteria on meat; Chicken Carcasses on the number of bacteria found on chicken meat; and on micro bacteria on beef in Kigali city, Rwanda [33,17,12]. [29,30,27].…”
Section: Enumeration Of Total Aerobic Bacteriasupporting
confidence: 81%
“…A higher prevalence of S. aureus in pigs and pork meat has been determined in other studies, with values ranging from 45 to 65% [20,51,52]. However, Tanih et al [53] detected a prevalence of S. aureus in carcasses around 13.0%, which is much lower than the prevalence found in this study.…”
Section: Prevalence Of Staphylococcus Aureus Strains In the Meat Suppcontrasting
confidence: 80%
“…Although DAEC was expected to preferentially colonize young children instead of adults (20), no significant correlation was found between DAEC infection and the age of afaB-positive patients. Tanih et al (42) reported that EIEC was not detected in cattle or pigs in South Africa. No virB from EIEC has been detected in our studies, suggesting that the risk of EIEC outbreaks should be negligible in Japan, as we have reported before (33,40).…”
Section: Discussionmentioning
confidence: 99%